Antimicrobial properties of local green seaweed (Caulerpa Racemosa) in Langkawi - Mohamad Isa, Habsah; Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah (2008)
The antimicrobial activity is widespread among marine seaweeds. However, antimicrobial defenses of marine micro algae are largely uncharacterized for locally available seaweed species. The aim of this study was to evaluate the antimicrobial activity of Caulerpa racemosa (‘Latok Lada’), an edible green seaweed species available in Langkawi Island, Kedah. Methanol extracts of the dried samples of C. racemosa was tested against Staphylococcus aureus, Escherichia coli, Pseudomonas aureginosa, Bacillus subtilis and MRSA (Methilcillin-resistant Staphylococcus aureus). Phosphate Buffer Saline (PBS) extracts of fresh sample of C. racemosa was tested against four different fungi; Candida albicans, Candida krusei, Candida tropicalis and Cryptococcus neoformans. C. racemosa showed good antibacterial activity against Gram-positive and Gram-negative bacteria tested, with a significant antimicrobial effect against B. subtilis (ZI=3-9mm), S. aureus (ZI=3-9mm), P. aureginosa (ZI=1-3mm) and MRSA (ZI=3-6mm). C. racemosa did not demonstrate any antifungal properties against any of the four fungi tested. Further studies needs to be performed on other types of bacteria and fungi as well as utilizing different extraction methods to further investigate the antimicrobial properties of C. racemosa. These preliminary results showed promising trend of antimicrobial properties in local seaweeds species collected in Langkawi coastline.